Treatable traits qualifying for nonpharmacological interventions in COPD patients upon first referral to a pulmonologist: the COPD sTRAITosphere. Issue 4 (2nd November 2020) - van 't Hul, Alex J.; Koolen, Eleonore H.; Antons, Jeanine C.; de Man, Marianne; Djamin, Remco S.; in 't Veen, Johannes C.C.M.; Simons, Sami O.; van den Heuvel, Michel; van den Borst, Bram; Spruit, Martijn A.
Introduction: The present study assessed the prevalence of nine treatable traits (TTs) pinpointing nonpharmacological interventions in patients with COPD upon first referral to a pulmonologist, how these TTs co-occurred and whether and to what extent the TTs increased the odds having a severely impaired health status. Methods: Data were collected from a sample of 402 COPD patients. A second sample of 381 patients with COPD was used for validation. Nine TTs were assessed: current smoking status, activity-related dyspnoea, frequent exacerbations <12 months, severe fatigue, depressed mood, poor physical capacity, low physical activity, poor nutritional status and a low level of self-management activation. For each TT the odds ratio (OR) of having a severe health status impairment was calculated. Furthermore, a graphic representation was created, the COPD sTRAITosphere, to visualise TTs prevalence and OR. Results: On average 3.9±2.0 TTs per patient were observed. These TTs occurred relatively independently of each other and coexisted in 151 unique combinations. A significant positive correlation was found between the number of TTs and Clinical COPD Questionnaire total score (r=0.58; p<0.001). Patients with severe fatigue (OR: 8.8), severe activity-related dyspnoea (OR: 5.8) or depressed mood (OR: 4.2) had the highest likelihood of having a severely impaired health status. The validation sample corroborated these findings. Conclusions: Upon first referral to a pulmonologist, COPD patients show multiple TTs indicating them to several nonpharmacological interventions. These TTs coexist in many different combinations, are relatively independent and increase the likelihood of having a severely impaired health status. Patients with COPD show numerous nonpharmacological treatable traits (TTs) upon referral to a pulmonologist. These TTs coexist in many different combinations, are relatively independent and increase the likelihood of a severely impaired health status. https://bit.ly/355mhpj